Elasto-plastic finite element analysis of metal-matrix composite plates with hole under plane loading - Okumuş, Fuat; Turgut, Aydin; Sancaktar, Erol (ASME, 1999)
The elasto-plastic stress analysis of composite plates with hole has been carried out by the finite element method. For this purpose, an isoparametric rectangular element with nine nodes has been chosen and the lagrange polynomial has been used as interpolation function. Steel-aluminum composite has been manufactured by using mould under the action of 30 MPa pressure and heating up to 600°C. Mechanical properties and yield strength of the composite material have been obtained experimentally by using a strain gauge in the tensile testing machine. The composite plates in various dimensions have been obtained by changing the diameter of the hole. The various tension loads which are increased step by step from beginning of the yield have been applied to these plates. The expansions of plastic regions have been illustrated for various cases. According to orientation angle and applied loads, elastic, plastic and residual stresses have been obtained.
Reliability, Stress Analysis, and Failure Prevention Issues in Adhesive and Bolted Connections - 1999 (The ASME International Mechanical Engineering Congress and Exposition) -- 14 November 1999 through 19 November 1999 -- Nashville, TN, USA -- 56783
Keywords: Aluminum; Elastoplasticity; Finite element method; Interpolation; Materials testing; Plate metal; Residual stresses; Steel; Strain gages; Stress analysis; Tensile testing; Yield stress; Isoparametric rectangular element; Lagrange polynomial; Metal matrix composite plates; Plane loading; Metallic matrix composites